Application of the CRONE control-design method to a low-frequency active suspension system. (17th May 2010) - Moreau, X.; Rizzo, A.; Oustaloup, A.
This paper presents a control law for a low-frequency active suspension system. The structure of the proposed control law is based on cooperation between feedforward and feedback. Feedforward design is based on the vehicle physics. The feedback law is synthesised from CRONE control-design method, French acronym of "Commande Robuste d'Ordre Non Entier" (non-integer order robust control). Modelling, robust control-design in frequency-domain, optimal approach, stability analysis and performance are presented in this paper.